Renoprotective impact of estrogen receptor-α and its splice variants in female mice with type 1 diabetes - Irsik, Debra L. (Am J Physiol Renal Physiol, 2018)
Estrogen has been implicated in the regulation of growth and immune function in the kidney, which expresses the full-length estrogen receptor-α (ERα66), its ERα splice variants, and estrogen receptor-β (ERβ). Thus, we hypothesized that these splice variants may inhibit the glomerular enlargement that occurs early in type 1 diabetes (T1D). T1D was induced by streptozotocin (STZ) injection in 8- to 12-wk-old female mice lacking ERα66 (ERα66KO) or all ERα variants (αERKO), and their wild-type (WT) littermates. Basal renal ERα36 protein expression was reduced in the ERα66KO model and was downregulated by T1D in WT mice. T1D did not alter ERα46 or ERβ in WT-STZ; however, ERα46 was decreased modestly in ERα66KO mice. Renal hypertrophy was evident in all diabetic mice. F4/80-positive immunostaining was reduced in ERα66KO compared with WT and αERKO mice but was higher in STZ than in Control mice across all genotypes. Glomerular area was greater in WT and αERKO than in ERα66KO mice, with T1D-induced glomerular enlargement apparent in WT-STZ and αERKO-STZ, but not in ERα66KO-STZ mice. Proteinuria and hyperfiltration were evident in ERα66KO-STZ and αERKO-STZ, but not in WT-STZ mice. These data indicate that ERα splice variants may exert an inhibitory influence on glomerular enlargement and macrophage infiltration during T1D; however, effects of splice variants are masked in the presence of the full-length ERα66, suggesting that ERα66 acts in opposition to its splice variants to influence these parameters. In contrast, hyperfiltration and proteinuria in T1D are attenuated via an ERα66-dependent mechanism that is unaffected by splice variant status.